2008
DOI: 10.1007/s11248-008-9202-7
|View full text |Cite
|
Sign up to set email alerts
|

In trangenic rice, α- and β-tubulin regulatory sequences control GUS amount and distribution through intron mediated enhancement and intron dependent spatial expression

Abstract: The genomic upstream sequence of the rice tubulin gene OsTub6 has been cloned, sequenced and characterized. The 5'UTR sequence is interrupted by a 446 bp long leader intron. This feature is shared with two other rice beta-tubulin genes (OsTub4 and OsTub1) that, together with OsTub6, group in the same clade in the evolutionary phylogenetic tree of plant beta-tubulins. Similarly to OsTub4, the leader intron of OsTub6 is capable of sustaining intron mediated enhancement (IME) of gene expression, in transient expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
0
33
0
Order By: Relevance
“…Although IDSE has been reported in some plant studies, the mechanism is still not clear (Giani et al, 2009;Jeong et al, 2007Jeong et al, , 2006Lu et al, 2008). The first intron of PhADF1 changes tissue-specific expression and deleting the 5 0 -upstream region alters the expression pattern (Jeong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although IDSE has been reported in some plant studies, the mechanism is still not clear (Giani et al, 2009;Jeong et al, 2007Jeong et al, , 2006Lu et al, 2008). The first intron of PhADF1 changes tissue-specific expression and deleting the 5 0 -upstream region alters the expression pattern (Jeong et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The 5UIs are important regulatory elements for controlling gene expression and are reported to change expression levels and locations in plants (Bicknell et al, 2012;Chorev and Carmel, 2012;Giani Our previous study showed that BmAPN4 is expressed in the entire midgut but expression of EGFP under the promoter P3P is only in the anterior midgut of P3 silkworms (Lu et al, 2012). To determine if the difference in expression was due to the 5UI of BmAPN4, we cloned P3Pþ5UI, which consisted of P3P and 5UI, and generated transgenic P3þ5UI silkworms (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upstream 5′UTR intron of α-tubulin genes is responsible for their expression (Fiume et al 2004). The 5′UTR intron in rice β-tubulin gene Ostub16 has also been used to enhance expression levels in rice (Giani et al 2009). Both transient expression (Hwang et al 2002) and transgenic analyses in rice seeds have showed a high level of target protein expression with the use of a portion of the native 5′UTR sequence of Gt1.…”
Section: Translational Efficiency and Role Of Untranslated Regionsmentioning
confidence: 99%
“…It is shown that introns also participate in the control of tissue speci city (Fu et al 1995;Gianì et al 2009;Jeon et al 2001;Jeong et al 2006) as well as the control of the expression level.…”
mentioning
confidence: 99%